Influence of Social Isolation During Prolonged Simulated Weightlessness by Hindlimb Unloading - Tahimic, Candice G. T.; Paul, Amber M.; Schreurs, Ann-Sofie; Torres, Samantha M.; Rubinstein, Linda; Steczina, Sonette; Lowe, Moniece; Bhattacharya, Sharmila; Alwood, Joshua S.; Ronca, April E.; Globus, Ruth K. (Frontiers in Physiology, 2019)
The hindlimb unloading (HU) model has been used extensively to simulate the cephalad fluid shift and musculoskeletal disuse observed in spaceflight with its application expanding to study immune, cardiovascular and central nervous system responses among others. Most HU studies are performed with singly housed animals, although social isolation also can substantially impact behavior and physiology, and therefore may confound HU experimental results. Other HU variants that allow for paired housing have been developed although no systematic assessment has been made to understand the effect of social isolation on HU outcomes. Hence, we aimed to determine the contribution of social isolation to tissue responses to HU. To accomplish this, we developed a refinement to the traditional NASA Ames single housing HU system to accommodate social housing in pairs retaining desirable features of the original design. We conducted a 30 day HU experiment with adult, female mice that were either singly or socially housed. HU animals in both single and social HU housing displayed expected musculoskeletal deficits versus housing matched, normally loaded (NL) controls. However, select immune and HPA axis responses were differentially impacted by the HU social environment relative to matched NL controls. HU led to a reduction in % CD4+ T cells in singly housed, but not in socially housed mice. Unexpectedly, HU increased adrenal gland mass in socially housed but not singly housed mice, while social isolation increased adrenal gland mass in NL controls. HU also led to elevated plasma corticosterone levels at day 30 in both singly- and socially housed mice. Thus, musculoskeletal responses to simulated weightlessness are similar regardless of social environment with a few differences in adrenal and immune responses. Our findings show that combined stressors can mask, not only exacerbate, select responses to HU. These findings further expand the utility of the HU model for studying possible combined effects of spaceflight stressors.